Naẓariyāt al-Ḥiyal fi al-Usrah al-Muslimah (Mazahib, 2016)
This article discusses ḥilah (plural: hiyal) or stratagem in Islamic family law. Hilah is one of the most important concepts in Islamic jurisprudence (fiqh). Hilah is simply defined as an attempt to manipulate the law and replace it with other rules without losing the essence of the law. The question that arises is what is the ruling of legal engineering in Islam? By means of normative study, this article presents the legal opinions regarding hilah in Islam. This study reveals that hilah can be divided into two kinds: Hilah Jaizah (allowed hilah) and Hilah Muharramah (forbidden hilah). Hilah jaizah is allowed in Islam by looking at certain conditions. In the context of Islamic family law, hilah can be done in such following conditions as: the bride's requirements of her prospective husband so as not to committing polygyny, and if that happens then the wife may sue him for divorce. Other conditions include when someone is allowed to admit to be infidel (kafir) for the sake of his/her family safety. Meanwhile, a case of hilah muharramah is doing tahlil marriageKeywords: Ḥilah in Islam, Islamic family law